Budgeting reconsidered: exploring change initiative in a bank. Issue 1 (3rd April 2019) - Valuckas, Danielius
Abstract : Purpose: This study aims to explore and understand a beyond budgeting-inspired initiative to abandon budgeting in a multinational bank. Design/methodology/approach: Analysing data from semi-structured interviews with actors involved in and affected by the change initiative, this paper draws on Kasurinen's accounting change framework as well as concepts from institutional theory to investigate the rationale for and the challenges of budget abandonment. Findings: Although the improving financial market stability and the increasing accountability of banks after the global financial crisis motivated the initial organisational changes, the appointment of a head of finance with experience of beyond budgeting was a major catalyst of change. This change-promoting leader was of utmost importance in providing relevant training and support, facilitating the change initiative and overcoming the initial resistance to change. However, the remnants of former budgeting practice did not regress as intended, and the change initiative stalled. Originality/value: This research contributes to beyond budgeting and accounting change studies by illustrating a stalled change initiative in the context susceptible to beyond budgeting ideas and highlighting the importance of aligning discourse and meaning with practice and routines.